Phorbol esters induce differentiation in human malignant T lymphoblasts - Nagasawa, Kohei (1980)
At nanomolar concentrations, phorbol ester, a class of potent tumor promoters, can promote differentiation in the human malignant T-lymphoblastic cell line MOLT-3. The optimal dose for induction, as measured by the increase of the number of cells containing sheep erythrocyte receptors (E-rosette assay), is between 8 and 16 nM 12-O-tetradecanoylphorbol 13-acetate (TPA), although there were significant increases of E-rosette-positive (E(+)) cells at concentrations as low as 1.6 nM TPA. The induction was linear for 4 days, then it reached a plateau. This induction was independent of the cell densities of the cultures, and the viability of the E(+) cells remained high (95-100%) even after 10 days of culture in the presence of the tumor promoters. The E(+) cells, when measured with the more stable 2-aminoethylisothiouronium bromide E-rosette assay, indicated that virtually all (75-95%) of the MOLT-3 cells became E(+) by 4 days in culture. This induction by TPA was also accompanied by a dramatic drop in the plating efficiencies and a reduction in DNA synthesis. Examination of phorbol and other phrobol esters indicated that the ability to induce these cells correlated well with the tumor-promoting activities of these compounds, because only TPA and to a lesser extent phorbol 12,13,-dibenzoate induced E(+) cells, while phorbol and 4α-phorbol 12,13-didecanoate had no effect. Studies of MOLT-3 cells depleted of E(+) cells indicated that the induction of E(+) cells cannot be explained solely on the basis of enrichment or stimulation of the background E(+) cells in MOLT-3 cultures. Finally, we have shown that TPA also affected another differentiation marker, the loss of the enzyme terminal deoxyribonucleotidyl transferase. Terminal transferase activities and percentages of terminal-transferase-positive cells in these cultures were reduced to as low as 1/10th in 4 days in the presence of 16 nM TPA.